El proceso administrativo de adopción frente al interés superior del niño, niña o adolescente en el cantón Guaranda provincia Bolívar, año 2021. - Chacha Gualpa, Nina Elizabeth (2022)
In the present investigation, the administrative process of adoption is specifically analyzed in the best interest of the child and adolescent in the canton of Guaranda, province of Bolívar; For this, there is true information provided by the Ministry of Economic and Social Inclusion itself. The problem of the present investigation lies and is concentrated in the delaying administrative phase of adoption in Ecuadorian legislation during the year 2021, which affected the best interests of the child or adolescent, since the State had to prioritize the reintegration of minors in quality of adoptable to a family for its correct integral development that would allow it to function in a healthy environment. The research carried out corresponds to a type of mixed research because it was necessary to apply the qualitative method and the quantitative method; the level of research is descriptive and correlational; In addition to that, scientific, dogmatic and documentary methods were applied; the types of historical and explanatory research were applied for its development, as well as the survey technique that was applied to the legal professionals of the Guaranda canton, province of Bolívar, for which a previously prepared questionnaire was applied as data collection instrument. In relation to the expected results, it was possible to determine that in the year 2021 there was an affectation on the principle of superior interest that children and adolescents enjoy, this due to the slowness of the administrative process of adoption that led to generating a disinterest of the people who wanted to adopt because the process lasted several years, and as a consequence of that the boy, girl and adolescent could not be reinserted into a family for their correct integral development.